Temporary Trade Shocks, Spatial Reallocation, and Persistence in Developing Countries : Evidence from a Natural Experiment in West Africa - Emran, M. Shahe; Shilpi, Forhad; Coulombe, Harold; Blankespoor, Brian (World Bank, Washington, DC, 2019)
In response to rising inequality following decades of trade liberalization, many countries are adopting trade restrictions. Can temporary trade restrictions have long-lasting effects on the spatial distribution of employment and resource allocation? To analyze this, this paper exploits the civil war in Côte d'Ivoire (2002-07), which disrupted access to the world market for two neighboring landlocked countries: Mali and Burkina Faso. The Ivorian war forced rerouting of trade from the Abidjan route to non-Abidjan routes. This paper builds a general equilibrium model where a subsistence-based autarkic hinterland coexists with an integrated segment, and there are two alternative routes to international markets. A trade shock to one route affects resource allocation in both routes by shifting the spatial margins of market integration and sectoral specialization. The effects are heterogeneous, depending on the pre-war market access of a location. The empirical analysis takes advantage of panel data and estimates the effects on structural change in employment on the non-Abidjan route using a triple difference design with location fixed effects. The areas that remain in autarkic equilibrium before and after the trade shock provide plausible estimates of the changes arising from long-term factors unrelated to the trade shock. The estimates show that the temporary trade shock created divergence between the Abidjan and non-Abidjan routes, with accelerated structural change in favor of manufacturing and services employment in the non-Abidjan route. This paper finds evidence of persistence in the effects through higher sunk investment in built-up density, agglomeration through concentration of skilled labor and greater public investment in complementary inputs such as electricity infrastructure (measured by nightlights density).